Associations of age, BMI, and renal function to cortisol after dexamethasone suppression in patients with adrenal incidentalomas - Olsen, Henrik; Olsen, Martin (Frontiers in Endocrinology, 2023)
Introduction: The specificity of cortisol after 1 mg dexamethasone (cortisolDST) ≥50 nmol/l as a criterion for mild autonomous cortisol secretion (MACS) is approximately 85% in patients with adrenal incidentalomas (AI). The aim was to study the associations of cortisolDST to age, BMI, and renal function. Methods: We studied 1129 patients with AI examined from 2005 to 2015 at Skåne University Hospital and Helsingborg Hospital. The covariates studied were gender, age, BMI, eGFR, treatment with inhalation steroids, size of the AI, and size of the smallest AI in patients with bilateral AI (set to 0 in unilateral AI). We used machine learning models to uncover potential non-linear associations. They were trained to fit the data and examined using feature importance analysis and partial dependence plots. Partial dependence plots show the marginal effect on cortisolDST of a covariate averaging over other covariates. Results: CortisolDST was strongly associated to the size of the AI and weaker associated to age, BMI, and eGFR according to the feature importance analysis. The partial dependence plots indicated relatively linear relationships for cortisolDST to age (positively) and eGFR (negatively). The association of cortisolDST to BMI was non-linear. At BMI below 30 kg/m2, cortisolDST was negatively associated to BMI but it was unchanged at higher BMI levels. Using linear regression, we found that cortisolDST increased 11% (95% CI, 7–14%) for each 10-year increase in age. In patients with BMI below 30 kg/m2, cortisolDST increased 23% (95% CI, 16–31%) for each 5 kg/m2 decrease in BMI. We found no association at BMI levels above 30 kg/m2. CortisolDST increased 9% (95% CI, 6–11%) for each 10 ml/min/1.73m2 decrease in eGFR. Conclusions: CortisolDST is positively associated to age, negatively to BMI if below 30 kg/m2, and negatively to eGFR. These associations should be considered before diagnosing MACS.